Tipologi Filsafat Islam Post Ibnu Rusyd - Hambali, R. Yuli Ahmad (Jurnal Filsafat "WISDOM", 2019)
This article presents an attempt to uncover evidence of philosophical traditions in the Islamic world that are agreed to "die" as alleged by some. Philosophical traditions in the Islamic world ended the conflict after al-Ghazali and the death of Ibn Rushd. Philosophical traditions in the Islamic world continue to live and develop, even here and there are being renewed. Some philosophers after al-Ghazali's attack and the death of Ibn Rushd even presented directions and corrections that were completely different from the tradition of thought that had previously been carried out. Search through various readings, and references show the typology and tendencies. This philosophical tradition with a completely different style, direction, and tendency reach its peak at the hands of Mulla Sadra. Mulla Sadra then referred to several experts as figures who succeeded in synthesizing the three traditions of thought that had once lived in Islam. In the end, this article presents a search for philosophical typologies that grew and developed after the al-Ghazali attack and the death of Ibn Rusyd.